2019
DOI: 10.1108/hff-10-2018-0563
|View full text |Cite
|
Sign up to set email alerts
|

Instabilities of SWCNT conveying laminar, incompressible and viscous fluid flow

Abstract: Purpose This study aims to study the transverse vibration and instabilities of the fluid-conveying single-walled carbon nanotubes (CNTs). To this purpose, the Euler–Bernoulli beam model is used. Also, the surface effects, small-size effects of the both fluid and structure and two different elastic mediums viscoelastic and Pasternak elastic are investigated. Design/methodology/approach To consider the nano-scale for the CNT, the strain-inertia gradient theory is used and to solve the governing equation of mot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 34 publications
(57 reference statements)
0
3
0
Order By: Relevance
“…By increasing the radius-to-length ratio, the DIR shifts to higher dimensionless excitation frequencies, and the unstable region becomes smaller. The extension of this paper for viscous fluid flow according to previous works (Mirkalantari et al, 2017;Saffari et al, 2017;Foroutan et al, 2018;Oveissi et al, 2016aOveissi et al, , 2016bOveissi and Ghassemi, 2018;Oveissi et al, , 2017Oveissi et al, , 2019Mohamadi et al, 2019) affords engineers a good option for fluid flow simulation. ) where:…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…By increasing the radius-to-length ratio, the DIR shifts to higher dimensionless excitation frequencies, and the unstable region becomes smaller. The extension of this paper for viscous fluid flow according to previous works (Mirkalantari et al, 2017;Saffari et al, 2017;Foroutan et al, 2018;Oveissi et al, 2016aOveissi et al, , 2016bOveissi and Ghassemi, 2018;Oveissi et al, , 2017Oveissi et al, , 2019Mohamadi et al, 2019) affords engineers a good option for fluid flow simulation. ) where:…”
Section: Discussionmentioning
confidence: 90%
“…The extension of this paper for viscous fluid flow according to previous works (Mirkalantari et al , 2017; Saffari et al , 2017; Foroutan et al , 2018; Oveissi et al , 2016a, 2016b; Oveissi and Ghassemi, 2018; Oveissi et al , 2018, 2017, 2019; Mohamadi et al , 2019) affords engineers a good option for fluid flow simulation.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, one of the topics discussed for practical applications is the behavior of systems with nano-fluidstructural interaction such as fluid conveying CNTs. [15][16][17][18] Size, condition of nano-materials, and nature of atomic bonds can affect the properties of the materials and systems. So far, many studies have shown the inaccuracy of classical theories, and it has been proved that very small-scale structures have different mechanical behavior, and they are length-scale dependent parameters.…”
Section: Introductionmentioning
confidence: 99%